Northern garden symphony: combining hardy perennials for blooms season - Warbelow, Cyndie, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2021)
Section I defines the terms that will assure we all have our feet on the ground in the same garden speaking the same language. Section II dives into the concept of perennial design and identifies the most important parameters to consider when choosing the players for a garden symphony. Section III introduces the concept of the Charts as a design tool to keep the garden symphony playing bright and clear all season long. Section IV walks the reader through the step-by-step design of five garden symphonies using the charts as a guide for choosing the players. Appendix A is easy to access, in-depth descriptions of all of the plants listed on the Charts. The last four appendices provide guidance on planning, planting, supplementing color and structure in a perennial garden, and maintaining perennials from season to season.--Provided by publisher.
Before We Begin -- What is a Northern Garden? -- Perennial, Annual, Herbaceous, Woody -- What Does it All Mean? -- Native Plants Versus Non-Natives -- Some Thoughts about Varieties -- Designing a Perennial Garden -- Design at the Macro Level -- Design at the Medium Level -- A Guide to the Charts -- Master Chart -- Bloom Time Charts -- Height Charts -- Color Charts -- Gardening with the Charts -- The Starter Garden -- The Chamomile Tea Garden -- The Espresso Garden -- The Chameleon Garden -- The Foliage Dominant Garden.
Keywords: Perennials -- Alaska; Gardens -- Design; Gardening -- Alaska; Color in gardening -- Alaska